Kerja-Kerja Penyelenggaraan Bangunan Masjid Lama - Zolkepli, Siti Nor Rasyidah; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2021)
Nowadays, maintenance work in Malaysia has been undertaken by those who are experienced in building maintenance with various technologies and methods used. The old mosque building is also a building that needs to be considered in the maintenance work because it has its history and identity to be maintained to the new generation. To maintain the function and operation of the building maintenance work must be carried out according to the function and importance of the building. There are three objectives of this study, namely to study the maintenance process of the old mosque building, to study the problems in the maintenance process of the old mosque building, and measures to overcome the problems that occur in the maintenance of the old mosque building. This study focuses on three (3) old mosques located in Malaysia, namely Sultan Abu Bakar Mosque, Johor Bahru, Johor, Sultan Ibrahim Muar Mosque, Johor and Zahir Mosque, Alor Setar, Kedah. The selected old mosque building is over 50 years old but can still be used for general use due to the effectiveness of the maintenance work carried out. The interview method was chosen to find out the maintenance process carried out and the problems faced by the management during the maintenance work of the three old mosque buildings. The results of the study found that the maintenance work method is done according to the standards set through the processes and procedures set by the government. Also, the study can find out the management measures from the building to facilitate the maintenance work of the old mosque building to do maintenance planning done to maintain the function of the old building in the long run. This situation can also attract the attention of those involved to know about the maintenance work to create a safe and conducive environment in the old mosque building.